Cassava breeding and varietal dissemination in Vietnam from 1975 to 2000 - Hoang, Kim; Pham, Van Bien; Tran, Ngoc Quyen; Tran Ngoc Ngoan; Trinh, Phuong; Kawano, Kazuo (International Center for Tropical Agriculture, 2001)
Cassava breeding and varietal dissemination in Vietnam initiated in 1975 after Vietnam was unified. The cassava program in Vietnam began to cooperate closely with CIAT and became part of the Asian Cassava Research Network in 1988. Thanks to the introduction of new highyielding varieties from Thailand and the adoption of improved cultural practices, cassava production in Vietnam has made remarkable progress. Before 1985, Gon, H34 and Xanh Vinh Phu were the most popular cassava varieties. Between 1986 and 1993, HL20, HL23 and HL24 were selected from a local germplasm collection by Hung Loc Agricultural Research Center (HARC) and these varieties have been grown extensively in South Vietnam, with areas of about 70,000 to 80,000 ha planted annually to these varieties. More recently, the Vietnam Cassava Research and Extension Network, working in close collaboration with CIAT, Vedan Vietnam Enterprise Corp. Ltd. and other cassava processing factories, obtained further achievements, especially in the area of breeding and varietal dissemination. Six new high-yielding varieties were recommended and disseminated for production during 1993-1999; these are KM94, KM60 and SM937-26 (three high-starch and high-yield varieties for industrial processing), and KM98-1, KM95-3 and KM95 (three multipurpose varieties suitable for food, feed and processing, with early harvestability and an extended harvest time). The growing areas of KM94 and other new improved varieties were about 60,000 ha in the crop year 1999/2000. The high-yield/high-starch varieties have brought to the producers additional benefits of about 787 billion Vietnamese dong (US$ 60.78 million) during the six years from 1994 to 1999 in five provinces: Dong Nai, Binh Phuoc, Binh Duong, Tay Ninh and Ba Ria-Vung Tau. More than one half of the additional benefits went directly to cassava farmers; the rest was shared among cassava processing factories and traders. At present, Vietnam has a large and promising cassava germplasm collection. In the future, new varieties will be developed in order to satisfy the demand for higher production and additional processing. The present research direction is to develop high-starch and high-yield varieties by introducing new breeding materials, crossing and applying biotechnology in breeding; to multiply planting material of new varieties; and to enhance the adoption of sustainable cassava production practices.